Tanpa Politik Tidak Ada Organisasi: Perspektif dari Manajemen Sumberdaya Manusia - Sareth Chhim (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1999)
In this article, the writer discusses the prevalence of politics in organisations from the perspective of human resource management. There are some reasons as to why political issues always present in organisational matters: unclear formulation of objectives, resources scarcity, changes in technology and environment, un-programmed decisions, and organisational development. Hence, political behaviours would have significant impacts on the practice of human resources development. It is identified that political behaviours would influence performance assessment and evaluation, remuneration and compensation, and career or promotions. To create a more effective organisation and ascertain that it would attain its goals, there is a need for specific managerial approach which would able to overcome negative aspects of political behaviours.